THU0443 Differential diagnosis between rheumatoid arthritis and peripheral spondylarthropathies: Usefulness of shoulders ultrasonography. (23rd January 2014) - Ottaviani, S.; Dawidowicz, K.; Palazzo, E.; Gill, G.; Hayem, G.; Meyer, O.; Dieudé, P.
Abstract : Background: The differential diagnosis between rheumatoid arthritis (RA) and peripheral spondylarthropathies (pSpA) could be difficult. A recent ultrasound study showed that ultrasonography (US) of hands might help the physician to differentiate psoriatic arthritis to RA (1). Objectives: To investigate the usefulness of shoulders US to differentiate RA and pSpA, in individuals having painful shoulders. Methods: 36 RA (EULAR/ACR 2010 criteria) patients and 32 SpA (ESSG criteria) patients with clinical involvement of shoulder joints were consecutively included in the study. All US examinations were performed by one trained rheumatologist. The following items were systematically assessed: gleno-humeral effusion, long head biceps tendon tenosynovitis, sub-acromial and sub-deltoid bursitis, acromio-clavicular synovitis and bone erosion. Results: A total of 36 RA patients (median age: 56.0 [44.5-62.4], 72% of female) and 32 SpA patients (median age: 45.5 [37.8-58.3], 47% of female) were assessed. Rheumatoid Factor and anti-CCP antibodies were found in 86% and 91% in RA patients, respectively and none in SpA patients. A higher frequency of acromio-clavicular synovitis was observed in pSpA (72% vs 6%, OR=43.4 [7.6-329.4], P<0.0001). RA patients had more frequently sub-acromial and sub-deltoid bursitis (67% vs 31%, OR=4.4 [1.4-14.0], P=0.008), long head biceps tendon tenosynovitis (47% vs 13%, OR=6.2 [1.6-26.3], P=0.005), gleno-humeral effusion (28% vs 3%, OR =11.9 [1.4-265.6], P=0.015) and bone erosion (53% vs 3%, OR=35.6 [4.1-755.9], P<0.0001). Conclusions: Our results suggest that painful shoulder is highly associated with the acromio-clavicular synovitis detected by US in pSpA. Thus, US might help the physician i) to differentiate RA and pSpA in patients with painful shoulders ii) to better define the structure requiring local corticosteroid injection. References: Gutierrez M, Filippucci E, Salaffi F, Di Geso L, Grassi W.Differential diagnosis between rheumatoid arthritis and psoriatic arthritis: the value of ultrasound findings at metacarpophalangeal joints level. Ann Rheum Dis. 2011 Jun;70(6):1111-4. Epub 2011 Mar 15. Disclosure of Interest: None Declared